Acinetobacter spp resistente a antimicrobianos carbapenêmicos isolados de Infecções Hospitalares de Corrente Sanguínea: Estudo do Projeto SCOPE Brasil - Luz, Adryella de Paula Ferreira [UNIFESP] (2010)
Main Objective: To evaluate the susceptibility profile to antibiotics carbapenems and ampicillin/sulbactam, and the carbapenemases production among bloodstream isolates of Acinetobacter spp. from hospitalized patients participating in the SCOPE Program, period of june 2007 to July 2009. Specific objectives: (i) to evaluate the susceptibility to imipenem, meropenem and ampicillin/sulbactam by agar dilution; (ii) to characterize the frequency and types of metalo-B-lactamases in the carbapenem resistant isolates; (iii) to determine the frequency of oxacillinases coding genes among the carbapenem resistant isolates. Material and Methods: 206 isolates from the first blood stream nosocomial infection from 16 medical centers from the 5 regions of the country were susceptibility tested by agar dilution for imipenem, meropenem and ampicillin/sulbactam. The carbapenem resistant isolates were submitted to Real time multiplex PCR for detection of MBL genes (blaIMP, blaVIM, blaSIM, blaSPM, blaGIM) and oxacillinases coding genes (blaOXA23-like, blaOXA24-like, blaOXA51-like, blaOXA58-like). The isolates carring blaIMP were typed by PFGE . Results and Conclusion: 63% of the isolates were resistant to carbapenems (imipenem CIM50 64 μg/mL e CIM90 256 μg/mL); meropenem (CIM50 32 μg/mL e CIM90 256 μg/mL) and 45% to ampicillin/sulbactam (CIM50 8 μg/mL e CIM90 64 μg/mL). 24 (18%) carbapenem resistant isolates showed blaIMP. 94 (74%) showed blaOXA23 and 26 (20%) showed only blaOXA51. The highest resistant rate to carbapenem was observed in the Northeast region and the lowest rate in the South region. Clonal hospital and inter-hospital dissemination was observed for IMP carring isolates but not among the different regions.